La question de l’authenticité des meubles et le problème de leur conservation dans le premier musée polonais de Puławy - Janusz Krawczyk (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The way the criterion of authenticity was being applied in the evaluation of material relics did depend, among other things, on the kind of object and on the nature of its cultural status metamorphoses. The issue is discussed on the example of two pieces of furniture from the first Polish museum. The author analyses possible sources of inspiration for the conservation practice of that time.